Analyzing Mobile Stock Trading Platforms and Their Impact on Individual Investors' Financial Performance - Vasantha Rao, Taidala; Mahendrababu, Yedukondala; Babu Vemula, Prasanth; Gowri Swetha, Kanuru Sankara; Mahendrababu, Yedukondala (International Journal of Psychosocial Rehabilitation, 2019)
As a fast-growing area in Finance, Information technology (IT) plays an important role in how traders trade online.Investigating whether online trading has a significant effect on financial returns and risks is central to this inquiry. Thisstudy, using perceived usefulness and satisfaction categories, addresses how the IT trading platform affects the trader’strading risk-taking behavior and stock portfolio performance. We examined two unique data sets: 2,726 proprietaryonline trading accounts and 178 professional investors’ field survey. The results revealed that while the perceivedusefulness category presented significant differences between the risk-taking groups and significant impact on stockportfolio performance, the satisfaction category showed no significant results.